(untitled) (Ukrainian Journal of Ophthalmology, 2026)
It is far from always that the many-sidedness of an outstanding person can completely be recognized, understood, and appreciated by his contemporaries. Much remains concealed in spite of publicity, availability, a great number of publications, etc. This is true for Academician V.P. Filatov, a most influential ophthalmologist of his time, a genius inventor, a talented physician and surgeon, a founder of the ophthalmological school in Ukraine, an irreplaceable leader of the largest Scientific Research Institute of Eye Diseases and Tissue Therapy initiated by him and named after him. At the same time he had many other talents: he wrote stories [1, 2] and poems [3], draw pictures [8], participated in many, as we would call them now, “social projects” as meetings of Odessa artist, literary, and other societies. V.P. Filatov had unquenchable optimism, ever-living creative energy, and willing to cultivate kindness and mercy. Contemporaries loved and appreciated Academician V.P. Filatov both as a professional ophthalmologist and as a friend and a man of high integrity standards. Here is a poem devoted to him by Alexander De Ribas in 1928.